Biological and cognitive theories explaining panic disorder: A narrative review - Kyriakoulis, Peter; Kyrios, Michael (Frontiers in Psychiatry, 2023)
The last review on theories explaining panic disorder was published over 10 years ago. The current narrative review summarizes and examines several theories of panic disorder (PD) including biological theories, including neurochemical factors, metabolic and genetic theories, respiratory and hyperventilation theories and cognitive theory. Biological theories have informed the development of psychopharmacological treatments; however, they may be limited in their utility given the efficacy of psychological treatments. In particular, behavioral and, more recently, cognitive models have garnered support due to the efficacy of cognitive-behavior therapy (CBT) in treating PD. The role of combination treatments has been found to be superior in the treatment of PD in particular cases, lending support for the need for an integrated approach and model for PD given that the etiology of PD is complex and multifactorial.